2009
DOI: 10.1002/pits.20391
|View full text |Cite
|
Sign up to set email alerts
|

Improving homework accuracy: Interdependent group contingencies and randomized components

Abstract: Homework is an often employed teaching strategy that has strong positive effects on academic achievement across grade levels, content areas, and student ability levels. To maximize academic learning, accuracy of homework should be addressed. The present investigation employed a multiple-baseline design across academic behaviors to examine the efficacy of randomization of the interdependent group contingency on the homework accuracy of six fourth-grade students enrolled in a general education class. Results dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Interdependent group contingencies have proven effective in increasing scores on spelling, math, and English assignments (Popkin & Skinner, 2003), increasing the number of items learned (e.g., identifying the states that comprise the Northwest Region) in social studies (Dugan, Kamps, Leonard, Watkins, Rheinberger, & Stackhaus, 1995), increasing the use of components related to creative writing (Maloney & Hopkins, 1973), increasing the number of correct Spanish word translations (Lloyd, Eberhardt, & Drake, 1996), increasing reading performance (Alric et al, 2007;Sharp & Skinner, 2004), and improving homework accuracy (Reinhardt, Theodore. Bray, & Kehle, 2009).…”
Section: Effects Of Interdependent Group Contingencies On Academic Pementioning
confidence: 99%
“…Interdependent group contingencies have proven effective in increasing scores on spelling, math, and English assignments (Popkin & Skinner, 2003), increasing the number of items learned (e.g., identifying the states that comprise the Northwest Region) in social studies (Dugan, Kamps, Leonard, Watkins, Rheinberger, & Stackhaus, 1995), increasing the use of components related to creative writing (Maloney & Hopkins, 1973), increasing the number of correct Spanish word translations (Lloyd, Eberhardt, & Drake, 1996), increasing reading performance (Alric et al, 2007;Sharp & Skinner, 2004), and improving homework accuracy (Reinhardt, Theodore. Bray, & Kehle, 2009).…”
Section: Effects Of Interdependent Group Contingencies On Academic Pementioning
confidence: 99%
“…Despite the importance of increasing on-task behavior or compliance with assigned tasks (Williamson et al, 2009), improvements in these behaviors do not necessarily result in increased academic productivity (Klein, 1979). Previous research on the effects of group contingences on both compliance and accuracy has been limited (Lynch et al, 2009;Reinhardt, Theodore, Bray, & Kehle, 2009). One possible reason for this gap in existing literature is the issue of motivational deficits and skill deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies of small groups of students have generally shown a positive and varying impact (Reinhardt et al 2009) or large effects for math accuracy (e.g., ES=1.65; Popkin and Skinner 2003). Interdependent group contingencies when used with class-wide interventions in a general education setting have demonstrated improved math accuracy and fluency, even with underachieving students (Hawkins et al 2009;Pigott et al 1986).…”
Section: Group-oriented Contingenciesmentioning
confidence: 96%